Jatropha tanjorensis a Flora of Southeast Nigeria: Isolation and Characterization of Naringenin and Validation of Bio-enhanced Synergistical Activity of α- Tocopherol Toward Clinical Isolates of Resistant Bacterial - Ijoma, Ikechukwu Kingsley; Ajiwe, Vincent Ishmael Egbulefu (Makara Journal of Science, 2022)
Jatropha tanjorensis is among the rich floras of Southeast Nigeria and used by ethnic people to treat infections and manage health conditions. Ethnomedicine has long been employed in the treatment of ailments caused by bacterial pathogens. Studies showed that the incorporation of synthetic α-tocopherol to an antibacterial agent improves its activity. However, knowledge about the antibacterial-enhanced activity of plant-based α-tocopherols, especially those isolated from Jatropha tanjorensis, is limited because of the different bioactivities of synthetic and natural α-tocopherols. To determine the phytochemicals in J. tanjorensis, we carried out the structural elucidation of its leaf extracts. Naringenin and α-tocopherol were identified based on nuclear magnetic resonance experiments. To validate the bio-enhanced activity of α-tocopherol, we profiled the crude extracts, naringenin, α-tocopherol, and 1:1 mixture of naringenin and α-tocopherol against the resistant strains of local clinical isolates of Escherichia coli, Klebsiella pneumoniae, Salmonella typhi, Streptococcus pneumoniae, and Staphylococcus aureus using the average diameter of the zone of inhibition (AVDZI), minimum inhibitory concentration, and minimum bactericidal concentration. The results showed that the crude leaf extract (≥ 10.2 ± 0.17 mm) and naringenin (≥ 8.1 ± 0.13 mm) exhibited viable antibacterial activities, but α-tocopherol (≤ 2.23 ± 0.12 mm) did not show any activity against all the bacteria assayed. In addition, the 1:1 mixture of naringenin and α-tocopherol (≥ 8.7 ± 0.13 mm) showed an improved AVDZI, which suggested the bio-enhanced synergistical activity of its crude extracts induced by α-tocopherol. The results of these research validate the claims by ethnomedicine practitioners on the efficacy of J. tanjorensis in the treatment of infections.